Lung Ageing, Inflammation and Telomere Attrition – The Trilogy in Chronic Obstructive Pulmonary Disease: The Interplay of Aging, Telomere Attrition, and Inflammation in the Pathogenesis of COPD (Journal of Advances and Scholarly Researches in Allied Education, 2019)
COPD is ranked as the third common cause of death and considered as a global epidemic, with increasing prevalence as populaces live longer as a result of decreased mortality from cardiovascular and infectious diseases. Cigarette smoking is considered to be the significant hazard factor for COPD worldwide, however in developing countries vulnerability to indoor air pollution and biomass smoke is also common especially in rural areas. Various studies have demonstrated that incidence and prevalence of COPD increase with age in all populations. These associations suggest that normal aging could contribute to the pathogenesis of COPD. Telomeres are the structure of repetitive nucleotide sequence which encompass the regions at the ends of chromosomes and aid in chromosomal stability by protecting the DNA against recombination and degradation. Telomere shortening is a well-known phenomenon in aging and decreased telomere length in circulating leukocytes in COPD has been exhibited in a few investigations. Aging and COPD are related with critical dysregulation of the immune system that prompts a chronic inflammatory response. The comparative genetic determinants and molecular mechanisms shared by COPD and aging propose that immunosenescence may add to the advancement of COPD.